Diliyan Nikolchev: Exarch Stephan underthe “care” of the Communist Security Services, Sofia: Military Publishing House 2016, 463 pp. - Poptodorov, Radko (Forum Theologicum Sardicense, 2025)
This book review presents a newly published study on the biography of Bulgarian Exarch Stephan during the early years of the Communist regime. The work is based on materials from newly opened archives.